Short term fat feeding rapidly increases plasma insulin but does not result in dyslipidaemia - Barzel, Benjamin; Weir, Jacquelyn M.; Meikle, Peter J.; Burke, Sandra L.; Armitage, James A.; Head, Geoffrey A. (Frontiers in Physiology, 2014)
Although the association between obesity and hypertension is well known, the underlying mechanism remains elusive. Previously, we have shown that 3 week fat feeding in rabbits produces greater visceral adiposity, hypertension, tachycardia and elevated renal sympathetic nerve activity compared to rabbits on a normal diet. Because hyperinsulinaemia, hyperleptinemia and dyslipidaemia are independent cardiovascular risk factors associated with hypertension we compared plasma insulin, leptin and lipid profiles in male New Zealand White rabbits fed a normal fat diet (NFD 4.3% fat, n = 11) or high fat diet (HFD 13.4% fat, n = 13) at days 1, 2, 3 and weeks 1, 2, 3 of the diet. Plasma concentrations of diacylglyceride (DG), triacylglyceride (TG), ceramide and cholesteryl esters (CE) were obtained after analysis by liquid chromatography mass spectrometry. Plasma insulin and glucose increased within the first 3 days of the diet in HFD rabbits (P <0.05) and remained elevated at week 1 (P <0.05). Blood pressure and heart rate followed a similar pattern. By contrast, in both groups, plasma leptin levels remained unchanged during the first few days (P >0.05), increasing by week 3 in fat fed animals alone (P <0.05). Concentrations of total DG, TG, CE and Ceramide at week 3 did not differ between groups (P >0.05). Our data show plasma insulin increases rapidly following consumption of a HFD and suggests that it may play a role in the rapid rise of blood pressure. Dyslipidaemia does not appear to contribute to the hypertension in this animal model.